Implementasi Fuzzy Logic Control Metode Mamdani pada Pengatur Nilai Ph Air dan Nutrisi Hidroponik - Huban Kabir; Yusep Romario; Sadiana Putra (Pusat riset dan Inovasi Nasional, 2026)
In this study, a device was designed and implemented to control the water pH and nutrient density (concentration) in a hydroponic system using the Mamdani method of fuzzy logic, thus maintaining nutrient solution parameters within an optimal range for plant growth. This system relies on three input values ​​obtained from a water pH sensor, a nutrient TDS sensor, and a flow meter. These three sensors are used to control four peristaltic motors, each of which functions to increase and decrease the pH and nutrient levels in the solution. The speed of the peristaltic pump motor, when the water pH is set at 6.5 and the nutrient concentration is set at 700 ppm, is influenced by the difference between the sensor reading and the set point. The greater the difference, the higher the peristaltic pump motor speed. Conversely, the smaller the difference between the sensor reading and the set point, the lower the peristaltic pump motor speed. Furthermore, the amount of water flowing through the pipe also influences the peristaltic pump motor speed.